Navigating the Editorial Gauntlet for Excellence in Radiology Publishing - Chander Mohan; Manphool Singhal; Ashish Verma (Indian Journal of Radiology and Imaging)
Any scientific journal of repute constantly strives to ensure the highest possible quality, integrity, and ethical standards of published research. This article attempts to the highlight multifaceted responsibilities of an Editor in Chief (EiC) and editors such as managing the peer review process, detecting plagiarism, and ensuring quality of selected manuscript before publication. The EiC also has to tackle issues of salami slicing, duplicate submissions, secondary publications, and guest and ghost authorship while adhering to constantly evolving guidelines of the International Committee of Medical Journal Editors (ICMJE) and the Committee on Publication Ethics (COPE). The EiC has to ensure adherence to journal guidelines, confidentiality in rigorous review by motivated reviewers, preventing reviewer burnout, incentivization of reviewers, and the review by biostatistician of manuscripts having large data set for appropriateness of statistical analysis. This article emphasizes the decision-making strategies to balance quality with timely publication, maintaining confidentiality, and managing conflicts of interest by the EiC. It also discusses the role of the EiC in educating prospective authors and residents on academic writing, and the optimal utilization of an advisory board to advance the journal's mission. Finally, the EiC's role in managing permissions for the reuse of published images, collaborating with editors of other journals, and enhancing the journal's indexing and impact factor is underscored. This article provides essential best practices for maintaining high ethical and publication standards in radiology journals and the maze that the editor has to wade through in ensuring all of these. In addition, the EiC needs to maintain the highest level of motivation throughout the tenure as it is an honorary responsibility undertaken voluntarily.